Critical Thinking Skills Improvement of Students Through Guided Inquiry Learning Model with Scientific Approach - Rheima Affilia; Laili Komariyah; Shelly Efwinda (Jurnal Ilmiah Pendidikan Fisika, 2023)
The COVID-19 pandemic pushed many schools to create hybrid learning systems due to drastic changes in the learning environment. Technology and knowledge have advanced swiftly in the 21st century. As the foundation of education, the school is expected to foster students' 4C skills, one of which is critical thinking. This study aimed to analyze how students' critical thinking skills changed after studying harmonic motion using the guided inquiry model and scientific approach. The study used a quantitative method with the pre-experimental design's one-group pre-test post-test procedure. A 10-question essay was used to obtain data from 31 students in grade X IPA 3. The findings indicated that students' critical thinking skills improved, with an N-Gain score of 0.72. As well as implications for this study, there were significant differences in critical thinking participants were educated with the T-test sample pair after using the santific suppression with the guided inquiry model.